Texture dependent shifting behavior of neutral layer in bending of magnesium alloys. (September 2019) - Ren, Weijie; Li, Jiaji; Xin, Renlong
Abstract: In this work, we report a texture dependent shifting behavior of neutral layer in bending of a Mg–3Al–1Zn (AZ31) alloy. The underline mechanism is revealed based on microstructure examinations, and is correlated to the yield asymmetry between the inner and outer regions. Then, a pole figure is built based on extensive viscoplastic self-consistent (VPSC) simulations, showing the trend of neutral layer shifting with texture. This is helpful for designing the stamping process of magnesium alloys. Graphical abstract: Unlabelled Image